Fault distribution and formation mechanism of a magnetic quiet zone in the northern South China Sea. (11th July 2016) - Liu, H.; Luan, X. W.; Guo, L. L.; Yue, B. J.; Zhang, L.; Ran, W. M.; Pan, J.
Abstract : A magnetic quiet zone (MQZ) is located in the ocean–continent transition zone in the northern South China Sea (SCS), according to ΔT magnetic anomaly data. Features of the gravity and magnetic anomalies in the MQZ are discussed by the multi‐scale wavelet decomposition method. Comprehensive boundary identification and fault analysis by analytic signal and normalized total horizontal derivative methods achieve some good effects in the northern SCS. The inversion results suggest a deep magnetic basement, a shallow Curie isothermal interface and thin magnetic layers. The average depth of the Curie isothermal interface is about 14–28 km in the northern SCS, and the thickness of the magnetic layer is about 6–10 km in the MQZ. The formation mechanism of the MQZ is discussed, and the thinning of the magnetic layer is considered as the origin of the MQZ in the northern SCS. The deep hot mantle materials were upwelled during the extension of the SCS, and the magnetic layer was demagnetized. In addition, the magnetic anomaly caused by thick Mesozoic sediments was very weak, and the NW–SE‐trending faults made the magnetic bodies fragmental. The distribution of major faults is consistent with the fluctuating changes of the Curie isothermal interface, and the faults in the MQZ are the upward intrusion channels of the deep hot materials. Copyright © 2016 John Wiley & Sons, Ltd.